An exploration of the 'pushy parent' label in educational discourse. Issue 2 (4th March 2017) - Beauvais, Clementine
Abstract : This article explores the ideological function of the derogatory label of 'pushy parent', which, since the 1980s, has been used considerably in journalistic, popular, political and academic discourses in the UK and the USA. 'Pushy parent' is not a descriptive term, but a conceptually vague label implying the existence of antagonistic agents intent on optimising their children's educational attainment. This label, it is argued here, masks structural inequalities in educational opportunities and outcomes by making those inequalities imputable to individual practices. The article first explores the distinction 'pushy parenting' sets up between 'fake' and 'real' intelligence, and 'deserved' and 'undeserved' educational achievement. However, it is difficult to draw clear boundaries between the behaviours covered by 'pushy parenting', and those covered by the 'ideal' parenting of neoliberal educational policy. To conclude, the function of the 'pushy parent' label as inoculation is explored, as well as its implications for the cultural politics of education.